Stability estimates for a twisted rod under terminal loads: a three-dimensional study - Majumdar, A; Prior, C; Goriely, A (2011)

(untitled)
The stability of an inextensible unshearable elastic rod with quadratic strain energy density subject to end loads is considered. A self-contained proof in terms of local energy minimizers is presented and optimal bounds are obtained for the problem.